2018
DOI: 10.12669/pjms.344.14808
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of small bowel perforations due to unusual causes

Abstract: Objectives:Although non-traumatic Small Bowel Perforations (SBPs) are rare, they have high rates of morbidity and mortality in case of late presentation. Aetiological factors vary across different geographical regions. In this paper, SBPs caused by anything other than trauma and other well-known causes are presented and the current literature is reviewed.Methods:The study was conducted at General Surgery Clinics of two different tertiary university hospitals between January 2008 and September 2016. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Our results showed that iatrogenic perforations (41.9%) were the main causes for small bowel perforations. In other studies, ischemic-obstructive causes or inflammatory-associated perforations were found to be the main origins of small bowel perforations [ 2 , 7 , 21 ]. We explain the different rates with geographic facts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results showed that iatrogenic perforations (41.9%) were the main causes for small bowel perforations. In other studies, ischemic-obstructive causes or inflammatory-associated perforations were found to be the main origins of small bowel perforations [ 2 , 7 , 21 ]. We explain the different rates with geographic facts.…”
Section: Discussionmentioning
confidence: 95%
“…According to the location of the perforation, intestinal secretions may retro- or intraperitoneally leak and result in remaining clinical symptoms [ 2 , 6 ]. Covered perforations of the duodenum are characterized by diffuse pain with positive renal positional palpitation when nerves are affected [ 7 ]. Free perforations into the abdominal cavity show clinically conspicuous symptoms of an acute abdomen and peritonism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient presented to the emergency room with severe respiratory failure following aspiration of high amounts of vomit due to an intestinal obstruction. Other complications of bezoars include intestinal perforation [ 8 ], intestinal intussusception [ 9 ], and obstructive jaundice in patients with biliodigestive anastomosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, o único exame específico é a endoscopia digestiva alta, pois avalia a existência direta de corpos estranhos em trato gastrointestinal alto. Porém, este procedimento possui algumas restrições, como a não visualização do duodeno de maneira adequada (Uzunoglu et al, 2018).…”
Section: Introductionunclassified

Bezoar misto gastrojejunal - Relato de caso

Andreza Fidélis Siqueira,
Alvarenga Soares,
Condori Leandro
et al. 2024
Rev. Saber Digital